2011
DOI: 10.1183/09031936.00086011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fruit and vegetable intake on oxidative stress and inflammation in COPD: a randomised controlled trial

Abstract: Epidemiological evidence supports a positive relationship between fruit and vegetable (FV) intake, lung function and chronic obstructive pulmonary disease (COPD). Increasing FV intake may attenuate the oxidative stress and inflammation associated with COPD.An exploratory randomised controlled trial to examine the effect of increased consumption of FV on oxidative stress and inflammation in moderate-to-severe COPD was conducted. 81 symptomatically stable patients with a habitually low FV intake (two or fewer po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 36 publications
1
61
1
2
Order By: Relevance
“…In particular, higher plasma lipid peroxidation has been associated with higher risk for progression in patients with COPD, while higher catalase and erythrocyte glutathione activities were associated with decreased risk of progression of this disease 29. Some studies, but not all,30 have found significant associations of high fruit and vegetable consumption with reduced levels of oxidative stress31 and inflammation parameters32 as well as with increased levels of antioxidant defence 31. It has been shown that intake of fruits and vegetables rich in vitamin C, β-carotene, flavonoids and other antioxidants is inversely correlated not only with oxidative stress parameters (urinary 8-iso prostaglandin F2α and F2-isoprostane) but also with inflammatory biomarkers (such as C reactive protein, interleukin-6, tumour necrosis factor-α and 15-keto-dihydro-PGF2α metabolite) 32.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, higher plasma lipid peroxidation has been associated with higher risk for progression in patients with COPD, while higher catalase and erythrocyte glutathione activities were associated with decreased risk of progression of this disease 29. Some studies, but not all,30 have found significant associations of high fruit and vegetable consumption with reduced levels of oxidative stress31 and inflammation parameters32 as well as with increased levels of antioxidant defence 31. It has been shown that intake of fruits and vegetables rich in vitamin C, β-carotene, flavonoids and other antioxidants is inversely correlated not only with oxidative stress parameters (urinary 8-iso prostaglandin F2α and F2-isoprostane) but also with inflammatory biomarkers (such as C reactive protein, interleukin-6, tumour necrosis factor-α and 15-keto-dihydro-PGF2α metabolite) 32.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the impact of nutritional therapy in COPD patients [35]. However, it is still unclear how specific dietary components may influence lung function [6] and important clinical outcomes in patients with COPD [7]. In focus of many studies is the possible relationship between nutritional intake, inflammation, and oxidative stress in patients with COPD [8].…”
Section: Introductionmentioning
confidence: 99%
“…A beneficial effect of increased FV intake on inflammatory markers has been demonstrated in some (40) , but not all (34) studies. In terms of intervention studies with endpoints related to other disease states, no effect of increased FV consumption has been demonstrated on oxidative stress and inflammation in chronic obstructive pulmonary disease (41) , while an effect of increased FV intake on response to vaccination in older people has recently been shown (42) .…”
Section: Fruit and Vegetable Intervention Studiesmentioning
confidence: 99%